A high whiteness fluororubber composition and its preparation method and application

Through the combination of perfluoroether rubber, soluble polytetrafluoroethylene, gas-phase white carbon black and boron nitride, a high whiteness fluoroelastic composition was prepared, which solved the high metal ion content and whiteness in traditional rubbers, taking into account both the sealing effect. The problem is that semiconductor sealing materials with low metal ions, high whiteness and low compression permanent deformation are achieved, suitable for semiconductor and medical fields.

CN118388949BActive Publication Date: 2024-12-13IC SEAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410641323.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2024-12-13
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

During semiconductor processing, traditional white rubber products have high metal ion content, which affects conductivity and sealing effect, and it is difficult to take into account the high whiteness requirements and low compression permanent deformation.

Method used

Using perfluoroether rubber, soluble polytetrafluoroethylene, gas-phase white carbon black and boron nitride, etc., the high-white fluoroelastic composition is prepared by mixing uniformly, vulcanizing and water-ground drying processes, replacing traditional white colorants and reducing Metal ion content and increase whiteness.

Benefits of technology

Semiconductor sealing materials that achieve low metal ion content, high whiteness and low compression permanent deformation are suitable for high temperature environments and are suitable for semiconductor and medical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0004853365620000011
    Figure HDA0004853365620000011
Patent Text Reader

Abstract

The present invention provides a high-whiteness fluororubber composition and its preparation method and application. The raw materials comprising the following components in parts by weight: 100-120 parts of perfluoroether rubber, 1-5 parts of soluble polytetrafluoroethylene, 0-8 parts of fumed silica, 1-5 parts of boron nitride, 1-2 parts of a crosslinking agent, and 0.1-0.2 parts of a crosslinking aid. In the high-whiteness fluororubber composition of the present invention, the reinforcing fillers, soluble polytetrafluoroethylene and fumed silica, do not contain metal ion components, ensuring that the obtained product has a lower metal ion content. Boron nitride is an inorganic nitride that can cause FFKM containing a nitrile system to be crosslinked. At the same time, boron nitride has a certain whitening effect, which can further improve the whiteness of the product. In the patent of the present invention, it can replace the traditional white colorant, eliminating the introduction of metal ions in the traditional white colorant. At the same time, boron nitride is an inorganic compound that can also act as a filler to achieve a reinforcing effect. The crosslinking aid can appropriately shorten the vulcanization time and improve production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor materials, and in particular to a high-whiteness fluororubber composition and a preparation method and application thereof. Background Art

[0002] Perfluoroether rubber is mainly composed of tetrafluoroethylene and perfluoroalkyl vinyl ether as the main monomers, copolymerized with a small amount of cross-linkable third monomer. It has significant chemical resistance, high temperature steam resistance, low release and precipitation, and plasma resistance. It is especially suitable for semiconductor, aerospace, medical and other industries.

[0003] Traditional rubber products are mostly single black, and white rubber products give people a feeling of "high cleanliness", which is easier to be recognized by the market in the field of semiconductor processing with higher cleanliness requirements. In order to obtain white and / or colored rubber products with very high surface requirements, the main method currently used is to add white colorants (CN 105694242 B), such as titanium dioxide, zinc barium white, zinc white, etc. However, with the increase in the number of conventional white colorants, the metal ion content in the product will increase. In the core processes of semiconductor manufacturing such as deposition and etching, the control of metal impurities is crucial. Metal impurities can affect the conductivity of semiconductors, resulting in reduced performance or failure. Therefore, the sealing products used in important semiconductor processing processes have very high requirements for the metal ion content contained. High whiteness fillers such as silica that do not contain metal ions can also increase the whiteness of the product, but as the number of parts increases, it will affect the compression permanent deformation of the sealing product. The higher the compression permanent deformation, the worse the sealing effect.

[0004] Therefore, the sealing rings used in the semiconductor processing process have low metal ion content, high whiteness (≥90), low compression permanent deformation (≤25%), high temperature resistance and other characteristics, which are more likely to be favored by the market. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a high-whiteness fluororubber composition and a preparation method and application thereof, so as to obtain a semiconductor sealing material with excellent comprehensive performance.

[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a high-whiteness fluororubber composition, comprising the following raw materials in parts by weight: 100-120 parts of perfluoroether rubber, 1-5 parts of soluble polytetrafluoroethylene, 0-8 parts of fumed silica, 1-5 parts of boron nitride, 1-2 parts of a crosslinking agent, and 0.1-0.2 parts of a co-crosslinking agent.

[0007] The present invention also provides a method for preparing the high-whiteness fluororubber composition as described above, comprising the following steps:

[0008] 1) uniformly mixing perfluoroether rubber, soluble polytetrafluoroethylene, fumed silica and boron nitride to obtain a masterbatch;

[0009] 2) adding a crosslinking agent and a crosslinking agent to the masterbatch obtained in step 1), vulcanizing the masterbatch to obtain a sulfur product, and storing the product for future use;

[0010] 3) The sulfur product after being parked in step 2) is subjected to secondary vulcanization, and then water-grinded and dried to obtain a high-whiteness fluororubber composition.

[0011] The present invention also provides a use of the high-whiteness fluororubber composition in the field of semiconductor processing.

[0012] The present invention also provides a semiconductor sealing ring, which is prepared from the high-whiteness fluororubber composition as described above.

[0013] As described above, the high whiteness fluororubber composition of the present invention has the following beneficial effects:

[0014] The high-whiteness fluororubber composition of the present invention has no metal ion components in the reinforcing fillers soluble polytetrafluoroethylene and fumed silica, which ensures that the obtained product has a low metal ion content. Boron nitride is an inorganic nitride that can cause the FFKM containing a nitrile system to produce crosslinks. At the same time, boron nitride has a certain whitening effect, which can further improve the whiteness of the product. In the patent of the present invention, it can replace the traditional white colorant, eliminating the introduction of metal ions in the traditional white colorant. At the same time, boron nitride is an inorganic compound and can also act as a filler to achieve a reinforcing effect. The auxiliary crosslinking agent can appropriately shorten the vulcanization time and improve production efficiency.

[0015] The O-type rubber ring prepared by this patent invention has the advantage of low metal ions, and the compression permanent deformation at a high temperature of 204°C is ≤25%, and the whiteness is ≥90. Combined with the chemical corrosion resistance and plasma resistance of FFKM itself, the O-type rubber ring prepared by this patent invention can be used in semiconductors, medical and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a product schematic diagram of the O-type rubber ring prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0017] Hereinafter, a high-whiteness fluororubber composition, a preparation method thereof, and an application embodiment are specifically disclosed in detail.

[0018] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0019] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0020] The reason why whiteness is pursued in the semiconductor field is, on the one hand, based on the customer's perception that the higher the whiteness, the better the product. On the other hand, when the wafer is fired at high temperature, it will absorb infrared. The higher the whiteness, the less infrared absorption will be, and the less heat absorption energy will be. The common practice is to add some white colorants. Fillers that do not contain metal ions, such as silica, can also increase the whiteness of the product, but as the number of parts increases, it will affect the compression permanent deformation of the sealed product. The higher the compression permanent deformation, the worse the sealing effect. Therefore, the sealing ring used in the semiconductor processing process has a low metal ion content, a high appearance whiteness (≥90), a low compression permanent deformation (≤25%), high temperature resistance and other characteristics, which are more likely to be favored by the market. The applicant of this application unexpectedly discovered that the reinforcing fillers used, soluble polytetrafluoroethylene and fumed silica, do not contain metal ion components, ensuring that the obtained product has a lower metal ion content. Boron nitride is an inorganic nitride that can crosslink FFKM containing a nitrile system. Boron nitride has a certain whitening effect, which can further improve the whiteness of the product. In the present invention, it can replace the traditional white colorant, eliminating the introduction of metal ions in the traditional white colorant. Boron nitride is an inorganic compound and can also act as a filler to achieve a reinforcing effect. The auxiliary crosslinking agent can appropriately shorten the vulcanization time and improve production efficiency. On this basis, the present invention is completed.

[0021] The first aspect of the present invention provides a high-whiteness fluororubber composition, comprising perfluoroether rubber, soluble polytetrafluoroethylene, fumed silica, boron nitride, a crosslinking agent, and a co-crosslinking agent.

[0022] The high whiteness fluororubber composition provided by the present invention comprises: 100-120 parts of perfluoroether rubber. Optionally, the perfluoroether rubber is 100-105 parts, 105-110 parts, 110-115 parts or 115-120 parts.

[0023] The perfluoroether rubber is a nitrile vulcanization system. The Mooney viscosity ML1+10, 121°C is 30-80. Optionally, the Mooney viscosity ML1+10, 121°C is 30-50, 50-80, 30-40, 40-50, 50-60, 60-70 or 70-80, etc. The size of the Mooney viscosity is determined by the molecular weight and molecular weight distribution of the elastomer, which can reflect the difficulty of processing the elastomer. The Mooney viscosity range of the elastomer used in this patent has good fluidity during the processing and molding process, is suitable for the manufacture of sealing rings, and has higher production efficiency.

[0024] In a preferred embodiment of the present invention, the perfluoroether rubber is obtained by copolymerization of tetrafluoroethylene (TFE), perfluoroalkyl vinyl ether (PAVE), and nitrile-containing vulcanization site monomer (CN-CSM). In a preferred embodiment of the present invention, the molar ratio of TFE / PAVE / CN-CSM is 60-70:30-40:0.2-3. The general formula of perfluoroalkyl vinyl ether is R f1 OCF = CF2, where R f1 =CF3(CF2) x , x is an integer of 1 to 3. In a preferred embodiment of the present invention, x is 1, a perfluoroalkyl vinyl ether, such as perfluoromethyl vinyl ether (PMVE).

[0025] The general formula of the nitrile-containing sulfur-site monomer is CF2=CFOR f2 (CF2) n -CN, where R f2 =(CF2CF(CF3)O) m , m is an integer of 0-5; n is an integer of 1-3. In a preferred embodiment of the present invention, n is 1 and m is 2, and the nitrile-containing sulfurization site monomer is such as perfluoro-8-cyano-5-methyl-3,6-dioxa-1-octene (8-CNVE).

[0026] The high whiteness fluororubber composition provided by the present invention comprises 1-5 parts of soluble polytetrafluoroethylene, optionally, 1-2 parts, 2-5 parts, 1-3 parts, 3-5 parts, 1-2 parts, 2-3 parts, 3-4 parts or 4-5 parts of soluble polytetrafluoroethylene.

[0027] The zero shear viscosity [η] of the soluble polytetrafluoroethylene is 3500-3800 Pas at 350° C. Optionally, the zero shear viscosity [η] of the soluble polytetrafluoroethylene is 3500-3600 Pas, 3600-3700 Pas or 3700-3800 Pas at 350° C.

[0028] Soluble polytetrafluoroethylene is a reinforcing filler that does not contain metal ions and has high purity.

[0029] Soluble polytetrafluoroethylene is also known as tetrafluoroethylene (TFE)-perfluoroalkoxy vinyl ether (PAVE) copolymer, abbreviated as PFA. Soluble polytetrafluoroethylene with this weight and zero shear viscosity can be dispersed more evenly in the elastomer, easily forming a "sea-island" structure, which is beneficial for reinforcement. Beyond this range, the fluidity of soluble polytetrafluoroethylene is limited, and the plasticity increases, affecting the elasticity of the vulcanized rubber.

[0030] The high-whiteness fluororubber composition provided by the present invention comprises 0-8 parts of fumed silica, optionally, 0-1 parts, 1-8 parts, 0-5 parts, 1-5 parts, 5-8 parts, 5-6 parts, 6-7 parts or 7-8 parts of fumed silica.

[0031] In a preferred embodiment of the present invention, the BET specific surface area of ​​the fumed silica is ≥30 m 2 / g, SiO2 content ≥ 99.8%. Optionally, the BET specific surface area of ​​fumed silica is 30 to 140 m 2 / g. For example, it can be 30 to 80 m 2 / g, 80~140m 2 / g, 30~50m 2 / g, 50~70m 2 / g, 70~90m 2 / g, 90~100m 2 / g, 100~120m 2 / g, 120~140m 2 / g, etc. The larger the BET specific surface area, the higher the degree of branching, the better the bonding with the elastomer, and the better the reinforcement effect. However, the higher the degree of branching, the worse the dispersion effect between white carbon blacks, and it is easy to produce agglomeration and cause stress concentration.

[0032] The high whiteness fluororubber composition provided by the present invention comprises 1-5 parts of boron nitride. Optionally, the boron nitride is 1-2 parts, 2-5 parts, 1-3 parts, or 3-5 parts.

[0033] The particle size of the boron nitride is less than 500 nm, and the purity of the boron nitride is ≥ 99.8%. Optionally, the particle size of the boron nitride is 100-150 nm, 150-250 nm, 250-400 nm, etc.

[0034] The boron nitride of the present invention is cubic silicon nitride. The use of boron nitride within the above range can not only be used as an inorganic nitride as a crosslinking agent to play a crosslinking role, but the inventors unexpectedly found that boron nitride has a whitening effect compared to other inorganic nitrides. If the weight exceeds the above part, boron nitride will agglomerate with each other due to its nanometer level and is difficult to disperse; if the particle size exceeds the above, boron nitride will not play the role of a crosslinking agent.

[0035] The high whiteness fluororubber composition provided by the present invention comprises 1-2 parts of a crosslinking agent. Optionally, the crosslinking agent is 1-1.5 parts or 1.5-2 parts.

[0036] The cross-linking agent is an inorganic nitride, such as silicon nitride, carbon nitride, etc. Wherein, the particle size of the silicon nitride is less than 500nm, and the content is ≥99.8%. Optionally, the particle size of the silicon nitride is 30-100nm.

[0037] In the high whiteness fluororubber composition provided by the present invention, the auxiliary crosslinking agent primary amine organic compound has the general formula R-NH2, wherein R is a non-benzene ring-containing structure. Optionally, the auxiliary crosslinking agent is selected from one or more of t-butyl carbamate (t-BCM), urea (Urea), biuret, acetic acid formamidine, etc. The applicant has screened the auxiliary crosslinking agent of the present invention after a lot of research, aiming to achieve the effect of crosslinking without affecting the color, shorten the vulcanization time, and improve production efficiency.

[0038] The properties of the high whiteness fluororubber composition of the present invention are any one or more of the following:

[0039] a) Compression set at 204°C ≤ 25%;

[0040] b) Whiteness ≥ 90;

[0041] c) Tensile strength ≥ 12MPa;

[0042] d) Elongation at break ≥ 130%;

[0043] e)T90≤15min.

[0044] A second aspect of the present invention provides a method for preparing the high whiteness fluororubber composition as described above, comprising the following steps:

[0045] 1) uniformly mixing perfluoroether rubber, soluble polytetrafluoroethylene, fumed silica and boron nitride to obtain a masterbatch;

[0046] 2) adding a crosslinking agent and a crosslinking agent to the masterbatch obtained in step 1), vulcanizing the masterbatch to obtain a sulfur product, and storing the product for future use;

[0047] 3) The sulfur product after being parked in step 2) is subjected to secondary vulcanization, and then water-grinded and dried to obtain a high-whiteness fluororubber composition.

[0048] In the preparation method of the high whiteness fluororubber composition of the present invention, in step 1), the perfluoroether rubber, soluble polytetrafluoroethylene, fumed silica, and boron nitride are mixed in an internal mixer. Optionally, the mixing is carried out at 80-90°C, 90-100°C, 80-85°C, 85-90°C, 90-95°C, or 95-100°C. In a preferred embodiment of the present invention, the mixing temperature is 80°C.

[0049] In step 1), after the mixing is uniform, the mixture is discharged at 90-110°C and 145-165°C on an open mixer for tableting, and left for more than 16 hours to obtain a masterbatch. The discharge temperature can be 90-100°C, 100-110°C, 90-95°C, 95-100°C, 100-105°C or 105-110°C. In a preferred embodiment of the present invention, the discharge temperature is 95°C.

[0050] In step 1), the parking time is greater than 16 hours.

[0051] In the preparation method of the high whiteness fluororubber composition of the present invention, in step 2), the masterbatch needs to be thin-passed on the open mill before adding the auxiliary crosslinking agent and the crosslinking agent. After the thin-passing, the left and right cutters are cut 2 to 4 times, 2 to 3 times or 3 to 4 times respectively, and the roll speed of the open mill is adjusted to 12 to 14 r / min, 12 to 13 r / min or 13 to 14 r / min for the front roll, 14 to 16 r / min, 14 to 15 r / min or 15 to 16 r / min for the rear roll, and then the roll distance is adjusted to 0.5 to 0.8 mm, 0.5 to 0.6 mm, 0.6 to 0.7 mm or 0.7 to 0.8 mm before adding the auxiliary crosslinking agent and the crosslinking agent. In a preferred embodiment of the present invention, after the thin-passing, the left and right cutters are cut 3 times respectively, and the roll speed of the open mill is adjusted to 12 r / min for the front roll, 14 r / min for the rear roll, and then the roll distance is adjusted to 0.6 mm before adding the auxiliary crosslinking agent and the crosslinking agent.

[0052] In step 2), after adding the auxiliary cross-linking agent and the cross-linking agent, the triangular package is formed at a roller distance of 0.3 to 0.5 mm, for example, the roller distance is 0.3 to 0.4 mm or 0.4 to 0.5 mm. In a preferred embodiment of the present invention, the triangular package is formed at a roller distance of 0.4 mm. The number of triangular packages is 15 to 20 times, for example, 15 to 16 times, 16 to 17 times, 17 to 18 times, 18 to 19 times or 19 to 20 times. In a preferred embodiment of the present invention, the number of triangular packages is 20 times.

[0053] In step 2), the plate vulcanization temperature is 180-190° C., for example, 155-160° C., 160-165° C., 165-170° C., 170-175° C., 175-180° C., 180-185° C. or 185-190° C. In a preferred embodiment of the present invention, the plate vulcanization temperature is 180° C.

[0054] In step 2), the plate vulcanization pressure is 10-15 MPa, for example, 10-11 MPa, 11-12 MPa, 12-13 MPa, 13-14 MPa or 14-15 MPa. In a preferred embodiment of the present invention, the plate vulcanization pressure is 11 MPa.

[0055] In step 2), the flat plate vulcanization time is T90min, where T90 is the positive vulcanization time, and the flat plate vulcanization time is specifically determined according to T90, for example, it can be 10-15min.

[0056] In step 2), the parking time is 16 to 20 hours, for example, 16 to 17 hours, 17 to 18 hours, 18 to 19 hours or 19 to 20 hours.

[0057] In the method for preparing the high whiteness fluororubber composition of the present invention, in step 3), the secondary vulcanization temperature is 250-290° C., for example, 230-240° C., 240-250° C., 250-260° C., 260-270° C., 270-280° C. or 280-290° C. In a preferred embodiment of the present invention, the secondary vulcanization temperature is 290° C.

[0058] In step 3), the secondary vulcanization time is 16-20 hours, for example 4-6 hours, 6-8 hours, 8-10 hours, 10-12 hours, 12-14 hours or 14-16 hours. In a preferred embodiment of the present invention, the secondary vulcanization time is 16 hours.

[0059] The preparation process of the high-whiteness fluororubber composition of the present invention is carried out in a dust-free workshop of Class 1000 or below. Semiconductor parts have relatively high requirements for product cleanliness. In ordinary processing workshops, there will be a large amount of impurities such as dust and bacteria, which affect the corrosion gas resistance of the sealing ring. The high-whiteness fluororubber composition prepared by the present invention is prepared in a dust-free workshop of Class 1000, which ensures the excellent corrosion gas resistance of the product.

[0060] The third aspect of the present invention provides a use of the high whiteness fluororubber composition as described above in the field of semiconductor processing. The high whiteness fluororubber composition can be made into a sealing ring, such as an O-type sealing ring.

[0061] A fourth aspect of the present invention provides a semiconductor sealing ring prepared from the high-whiteness fluororubber composition as described above.

[0062] In the following examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.

[0063] The manufacturer of nitrile vulcanization system perfluoroether rubber is SOLVAY, brand PFR1055B.

[0064] Silicon nitride (α phase, 50 nm) was purchased from Admas, CAS No. 12033-89-5.

[0065] Boron nitride (hexagonal, 150 nm) was purchased from Admas, CAS No. 10043-11-5.

[0066] Soluble polytetrafluoroethylene, brand MJ-102, purchased from Mitsui DuPont, CAS No. 26655-00-5.

[0067] Basic fumed silica, brand NA50H, purchased from Evonik, CAS No. 199876-44-3.

[0068] Acidic fumed silica, brand R972, purchased from Evonik, CAS No. 68611-44-9.

[0069] The manufacturer of tert-butyl carbamate was Admas Company, CAS No. 4248-19-5.

[0070] The manufacturer of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane was Aladdin Reagent Company, CAS No. 83558-87-6.

[0071] Example 1

[0072] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0073] 1) In a Class 1000 dust-free workshop, add 100 parts of PFR1055B perfluoroether rubber into an internal mixer at 80°C. After the rubber compound is stable, add 5 parts of MJ-102 soluble polytetrafluoroethylene and 5 parts of (hexagonal crystal, 150nm) boron nitride into the internal mixer. After mixing evenly, discharge the rubber at a temperature of 95°C. Press the rubber into sheets on an open mixer and leave for 18 hours to obtain a masterbatch.

[0074] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0075] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0076] Example 2

[0077] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0078] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stable, 5 parts of MJ-102 soluble polytetrafluoroethylene, 8 parts of NA50H fumed silica (hexagonal crystal), and 2 parts of 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0079] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0080] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0081] Example 3

[0082] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0083] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 5 parts of MJ-102 soluble polytetrafluoroethylene, 5 parts of NA50H fumed silica, and 1 part of hexagonal crystalline, 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0084] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 1 part of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangular packages are made 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0085] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0086] Example 4

[0087] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0088] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 5 parts of MJ-102 soluble polytetrafluoroethylene, 5 parts of NA50H fumed silica, and 2 parts of hexagonal 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0089] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0090] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0091] Example 5

[0092] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0093] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 5 parts of MJ-102 soluble polytetrafluoroethylene, 5 parts of R972 fumed silica, and 2 parts of hexagonal 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0094] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0095] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0096] Example 6

[0097] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0098] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 1 part of MJ-102 soluble polytetrafluoroethylene, 5 parts of NA50H fumed silica, and 2 parts of hexagonal 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0099] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0100] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0101] Example 7

[0102] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0103] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 5 parts of MJ-102 soluble polytetrafluoroethylene, 5 parts of NA50H fumed silica, and 5 parts of hexagonal 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0104] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 5 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0105] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0106] Example 8

[0107] This embodiment provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0108] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 5 parts of MJ-102 soluble polytetrafluoroethylene, 5 parts of NA50H fumed silica, and 2 parts of hexagonal 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0109] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters cut 3 times each, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.1 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packages are made 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0110] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0111] Comparative Example 1

[0112] This comparative example provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0113] 1) In a Class 1000 dust-free workshop, add 100 parts of PFR1055B perfluoroether rubber into an 80°C internal mixer. After the rubber compound is stable, add 5 parts of MJ-102 soluble polytetrafluoroethylene and 5 parts of hexagonal 150nm boron nitride into the internal mixer. After mixing evenly, discharge the rubber at a temperature of 95°C. Press the rubber into sheets on an open mixer and leave for 18 hours to obtain a masterbatch.

[0114] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller distance is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent are added in sequence, and triangular packages are made 20 times at a roller distance of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min. The sulfur product obtained after the flat plate vulcanization is parked for 16h for standby use;

[0115] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0116] Comparative Example 2

[0117] This comparative example provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0118] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an internal mixer at 80°C. After the rubber compound was stabilized, 5 parts of MJ-102 soluble polytetrafluoroethylene, 10 parts of NA50H fumed silica, and 2 parts of hexagonal crystalline, 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0119] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0120] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0121] Comparative Example 3

[0122] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an 80°C internal mixer. After the rubber compound was stable, 10 parts of MJ-102 soluble polytetrafluoroethylene, 5 parts of NA50H fumed silica, and 2 parts of hexagonal 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0123] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters each cutting 3 times, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of t-BCM co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby;

[0124] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0125] Comparative Example 4

[0126] This comparative example provides a high whiteness fluororubber composition, and the preparation method thereof comprises the following steps:

[0127] 1) In a Class 1000 dust-free workshop, 100 parts of PFR1055B perfluoroether rubber were added to an 80°C internal mixer. After the rubber compound was stable, 5 parts of MJ-102 soluble polytetrafluoroethylene, cubic crystal, and 5 parts of 150nm boron nitride were added to the internal mixer. After mixing evenly, the mixture was discharged at a temperature of 95°C. The mixture was pressed on an open mixer and left for 18 hours to obtain a masterbatch.

[0128] 2) The masterbatch obtained in step 1) is thin-passed on an open mill, with the left and right cutters cut 3 times each, the roller speed is 12r / min for the front roller and 14r / min for the rear roller, the roller spacing is adjusted to 0.6mm, 2 parts of silicon nitride (α phase, 50nm) cross-linking agent and 0.2 parts of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane co-cross-linking agent are added in sequence, and triangle packing is performed 20 times at a roller spacing of 0.4mm, and sheets are produced; the flat plate is vulcanized in a Class 1000 dust-free workshop, the vulcanization temperature is 180°C, the vulcanization pressure is 11MPa, and the vulcanization time is T90min, and the sulfur product obtained after the flat plate vulcanization is parked for 16h for standby use;

[0129] 3) Put the product of step 2) after being parked into an oven for secondary vulcanization at a vulcanization temperature of 290° C. for 16 hours. The product obtained after disulfurization is dried by water mill to obtain a high-whiteness fluororubber composition.

[0130] As shown in Table 1, the component contents of each embodiment and comparative example are as follows:

[0131] Table 1

[0132]

[0133] Performance Testing:

[0134] The high whiteness fluororubber compositions obtained in each embodiment and comparative example were subjected to performance tests, and the performance test standards and methods are as follows:

[0135] Test M according to "ASTM D6601 Standard Test Method for Rubber Properties—Measurement of Cure and After-Cure Dynamic Properties Using a Rotorless ShearRheometer" H 、M L , T90, test conditions: 180℃, 30min.

[0136] According to GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, the tensile strength and elongation at break of rubber materials are tested;

[0137] According to GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, the tensile strength and elongation at break are tested.

[0138] The compression permanent deformation properties of rubber materials were tested according to ASTM D395-03 Standard test methods for rubber property-Compression Set; sample size: AS568-214 O-ring; test conditions: 204℃, 70h.

[0139] Test the whiteness of O-rings according to ASTM E313-10 Standard Practice for Calculating Yellowness and Whiteness Indices from Instrumentally Measured Color Coordinates.

[0140] The properties of the high whiteness fluororubber compositions of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 2:

[0141] Table 2

[0142]

[0143] Combined with Table 2, by comparing Comparative Example 1 with Examples 1-8, it can be seen that if no cross-linking agent is added to the formula system, the longer the positive vulcanization time (t90), the longer the processing time, which is not conducive to production and processing efficiency. However, the cross-linking agent 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane in Comparative Example 4 contains a benzene ring structure, and the color of the O-ring after vulcanization is deepened to a whiteness of 42.07, which cannot meet the requirements. The number of parts of fumed silica in Comparative Example 2 exceeds 8 parts, and the number of parts of soluble polytetrafluoroethylene in Comparative Example 3 exceeds 5 parts. Although the whiteness meets the requirements, the compression permanent deformation is greater than 25%, and the sealing effect is poor, which is not suitable for scenes with high sealing requirements.

[0144] In summary, the high whiteness fluororubber composition of the present invention, the reinforcing filler soluble polytetrafluoroethylene and fumed silica do not contain metal ion components, ensuring that the prepared product has a low metal ion content. Boron nitride is an inorganic nitride that can cause FFKM containing a nitrile system to produce crosslinks. At the same time, boron nitride has a certain whitening effect, which can further improve the whiteness of the product. In the patent of the present invention, it can replace the traditional white colorant, eliminating the introduction of metal ions in the traditional white colorant. At the same time, boron nitride is an inorganic compound and can also act as a filler to achieve a reinforcing effect. The auxiliary crosslinking agent can appropriately shorten the vulcanization time and improve production efficiency.

[0145] The O-type rubber ring prepared by this patent invention has the advantage of low metal ions, and the compression permanent deformation at a high temperature of 204°C is ≤25%, and the whiteness is ≥90. Combined with the chemical corrosion resistance and plasma resistance of FFKM itself, the O-type rubber ring prepared by this patent invention can be used in semiconductors, medical and other fields.

[0146] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high whiteness fluororubber composition, characterized in that: The raw materials include the following components in parts by weight: Perfluoroether rubber 100-120 parts, soluble polytetrafluoroethylene 1-5 parts, fumed silica 0-8 parts, boron nitride 1-5 parts, crosslinking agent 1-2 parts, co-crosslinking agent 0.1-0.2 parts; The perfluoroether rubber is a nitrile-based vulcanization system; the particle size of the boron nitride is less than 500 nm; The cross-linking agent is one or both of silicon nitride and carbon nitride; The auxiliary cross-linking agent is selected from one or more of tert-butyl carbamate, urea, biuret, and formamidine acetate.

2. The high whiteness fluororubber composition according to claim 1, characterized in that: The Mooney viscosity of the perfluoroether rubber ML1+10 at 121°C is 30-80.

3. The high whiteness fluororubber composition according to claim 1, characterized in that: The zero shear viscosity [η] of the soluble polytetrafluoroethylene is 3500-3800 Pas at 350°C.

4. The high whiteness fluororubber composition according to claim 1, characterized in that: The BET specific surface area of ​​the fumed silica is ≥30 m 2 / g, SiO2 content ≥99.8%.

5. The high whiteness fluororubber composition according to claim 1, characterized in that: The purity of the boron nitride is ≥99.8%.

6. The high whiteness fluororubber composition according to claim 1, characterized in that: The particle size of the silicon nitride is less than 500 nm, and the content is greater than or equal to 99.8%.

7. The high whiteness fluororubber composition according to any one of claims 1 to 6, characterized in that: The properties of the high whiteness fluororubber composition are any one or more of the following: a) Compression set at 204°C ≤ 25%; b) Whiteness ≥ 90; c) Tensile strength ≥ 12MPa; d) Elongation at break ≥ 130%; e)T90≤15min.

8. The method for preparing a high whiteness fluororubber composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) uniformly mixing perfluoroether rubber, soluble polytetrafluoroethylene, fumed silica and boron nitride to obtain a masterbatch; 2) adding a crosslinking agent and a crosslinking agent to the masterbatch obtained in step 1), vulcanizing the masterbatch to obtain a sulfur product, and storing the product for standby use; 3) The sulfur product after being parked in step 2) is subjected to secondary vulcanization, and then water-grinded and dried to obtain a high-whiteness fluororubber composition.

9. The method for preparing a high whiteness fluororubber composition according to claim 8, characterized in that: In step 1), the perfluoroether rubber, soluble polytetrafluoroethylene, fumed silica and boron nitride are mixed at 80-100° C.; And / or, in step 1), after the mixing is uniform, the mixture is discharged at 90-110° C. to an open mixer for tableting, and left for more than 16 hours to obtain a masterbatch; And / or, in step 2), before adding the auxiliary cross-linking agent and the cross-linking agent, the masterbatch needs to be thin-passed on the open mill, and after the thin-passing, the left and right cutters are cut 2 to 4 times each, and the roll speed of the open mill is adjusted to 12 to 14 r / min for the front roll and 14 to 16 r / min for the rear roll, and then the roll distance is adjusted to 0.5 to 0.8 mm before adding the auxiliary cross-linking agent and the cross-linking agent; And / or, in step 2), the plate vulcanization temperature is 180-190°C; And / or, in step 2), the plate vulcanization pressure is 10-15 MPa; And / or, in step 2), the plate vulcanization time is T90min; And / or, in step 2), the parking time is 16 to 20 hours; And / or, in step 3), the secondary vulcanization is carried out in an oven; And / or, in step 3), the secondary vulcanization temperature is 250-290°C; And / or, in step 3), the secondary vulcanization time is 16-20h.

10. Use of the high whiteness fluororubber composition according to any one of claims 1 to 7 in the semiconductor and medical fields.

Citation Information

Patent Citations

  • Colored or white rubber whitening agent titanium dioxide pre-dispersed masterbatch and its preparation method

    CN105694242B

  • Perfluoroether rubber composition as well as preparation method and application thereof

    CN114181484A

  • Low-corrosivity fluorine-containing sealing ring composition and preparation method thereof

    CN117534929A